Introduction and evaluation of blueberry cultivars for the state of ceará - Castro , Vitória de Oliveira; Ribeiro Nunes, Débora Cristina; da Silva , Francisco Iarle; Lopes de Sousa Cavalcante, Francisco Abidênago; Moraes de Lima, José Ayron; Luz, Lucas Nunes da (Comunicata Scientiae, 2025)
Blueberry is a crop commonly associated with temperate climates. Depending on the species, it may appear as semi-prostrate plants, shrubs, or small trees of varying heights. With the emergence of cultivars from the Southern Highbush group, several countries in the Southern Hemisphere have invested in blueberry cultivation, driven by global demand, economic profitability, and the versatile use of the fruit, especially considering its nutraceutical properties. Blueberries are a high-value fruit with strong market potential, which has led to increased local interest in cultivation, encouraged by state policies that promote crop diversification to enhance the value of agricultural production in the state. This study aims to provide data to support blueberry cultivation in the state of Ceará. Three blueberry cultivars (Biloxi, Biloxi XL, and Emerald) were evaluated under the climatic conditions of the Baturité massif region. Five morphological descriptors and nine productive descriptors were analyzed. Regarding productive aspects, ‘Biloxi’ achieved the best results in terms of fruit size and quantity. The Biloxi cultivar demonstrated greater hardiness under climatic conditions. Alternative cultivation systems to fertigation require further research, as inadequate practices may prevent cultivars from reaching their maximum productive potential.